2013 IEEE Congress on Evolutionary Computation 2013
DOI: 10.1109/cec.2013.6557627
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an energy harvesting buoy for coral reef monitoring

Abstract: The sustainable management of coastal and offshore ecosystems, such as for example coral reef environments, requires an energy efficient collection of accurate data across various temporal and spatial scales. To suitably address the energy supply of marine sensors, in this paper a novel energy harvesting device is proposed, based on a Tubular Permanent MagnetLinear Generator (TPM-LiG). The application is related to the sea wave energy conversion for small sensorized buoy. The optimization process is developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A buoy normally consists of a wireless sensor network node (CPU, sensors, radio, and batteries), an energy harvesting module, underwater sensors and a mooring system. For example, Pirisi et al [ 78 ] proposed a special energy harvesting buoy which can effectively use sea wave energy conversion as a power source and has potential applications in marine environment monitoring. Albaladejo et al [ 59 ] designed a multisensory buoy system which can be effectively used for shallow marine environment monitoring.…”
Section: Research Challenges and Opportunitiesmentioning
confidence: 99%
“…A buoy normally consists of a wireless sensor network node (CPU, sensors, radio, and batteries), an energy harvesting module, underwater sensors and a mooring system. For example, Pirisi et al [ 78 ] proposed a special energy harvesting buoy which can effectively use sea wave energy conversion as a power source and has potential applications in marine environment monitoring. Albaladejo et al [ 59 ] designed a multisensory buoy system which can be effectively used for shallow marine environment monitoring.…”
Section: Research Challenges and Opportunitiesmentioning
confidence: 99%
“…Depending on the purpose, direct driven point absorber system can be realized over the vast scale of power capacities, ranging from few tents of watts to megawatts [Pirisi, 2010& Mueller, 2002. Various studies have shown potential of small direct driven wave energy converters to satisfy energy needs of the marine communication, surveillance and signalization equipment in a persistent and sustainable manner [Pirisi, 2013]. Right now, it seems that those small power consumers might be the most suitable first assignment for the developing point absorbers technology.…”
Section: Direct Driven Point Absorbermentioning
confidence: 99%
“…Some recent research papers focus on optimization of these linear generators, such as the graphical optimization is presented in [16] for an iron-less and brush-less PMLG. The optimization of two tubular PMLGs for OWE conversion are presented in [17] optimization of a superconducting racetrack magnet for the rotor of a wind-farm generator is described in [18]. However, the shape optimization of the stator and translator as shown in [19] and [20] greatly affects and improves different electrical and magnetic parameters of the linear generator.…”
Section: Introductionmentioning
confidence: 99%